2002
DOI: 10.4049/jimmunol.169.7.3686
|View full text |Cite
|
Sign up to set email alerts
|

T Cells Primed byLeishmania majorInfection Cross-React with Alloantigens and Alter the Course of Allograft Rejection

Abstract: Alloreactive T lymphocytes can be primed through direct presentation of donor MHC:peptide complexes on graft cells and through indirect presentation of donor-derived determinants expressed by recipient APCs. The large numbers of determinants on an allograft and the high frequency of the alloreactive repertoire has further led to speculation that exposure to environmental Ags may prime T cells that cross-react with alloantigens. We sought to develop a model in which to test this hypothesis. We found that CD4+ T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
126
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(130 citation statements)
references
References 59 publications
4
126
0
Order By: Relevance
“…Our current study explored a novel aspect of memory CD8 T cells, i.e., CD154 costimulation blockade-resistant activation. We and others (9,(33)(34)(35) have demonstrated that alloreactive CD8 T cells in the absence of CD4 help fail to develop this phenotype, as reactivation of helpless alloreactive CD8 memory T cells remains susceptible to the CD154 blockade suggesting that these cells are functionally naive.…”
Section: Discussionmentioning
confidence: 99%
“…Our current study explored a novel aspect of memory CD8 T cells, i.e., CD154 costimulation blockade-resistant activation. We and others (9,(33)(34)(35) have demonstrated that alloreactive CD8 T cells in the absence of CD4 help fail to develop this phenotype, as reactivation of helpless alloreactive CD8 memory T cells remains susceptible to the CD154 blockade suggesting that these cells are functionally naive.…”
Section: Discussionmentioning
confidence: 99%
“…Experimental animal models have revealed that the exposure of hosts to viral or parasitic agents prior to transplantation can result in the development of memory T cells (5)(6)(7) that are resistant to the effects of anti-CD154 therapy (8,9). A subset of these pathogen-specific memory T cells has been shown to cross-react, by molecular mimicry, with alloantigen presented by donor or recipient MHC molecules (10).…”
Section: Linical Data Support a Correlation Between Viral Infectionsmentioning
confidence: 99%
“…For example, mouse T-cell clones that are specific to poly(Glu60,Ala30,Tyr10), pigeon cytochrome c or sheep insulin can respond to a variety of allogeneic stimulator cells with a very high frequency (61% responded to at least one allogeneic haplotype, and 39% responded to more than one allogeneic stimulator). 1 In animal models, infection of B6 mice with Leishmania major can induce vigorous rejection of P/J skin allografts, 5 suggesting that T cells activated by the parasitic antigens can readily attack the skin allografts. Moreover, mice challenged with lymphocytic choriomeningitis virus prior to or concurrently with skin transplantation can significantly accelerate allograft rejection and prevent transplantation-tolerance induction.…”
Section: Specificity and Plasticity Of Tcrsmentioning
confidence: 99%
“…Besides T cells that are intrinsically reactive to alloantigens, a considerable fraction of T cells that are programmed to respond to nominal antigens can also be crossreactive to alloantigens. [4][5][6] Importantly, recent studies have convincingly demonstrated that certain memory T cells that are specific to conventional pathogens are highly alloreactive in transplant models. 3 The crossreactive nature of alloreactive T cells clearly highlights the flexibility of T-cell receptors (TCR) in their recognition of transplant antigens.…”
Section: Introductionmentioning
confidence: 99%